Effect of standoff distance and traverse speed on the cutting quality during the abrasive water jet machining (AWJM) of brass - Abouzaid, Abdelrahman; Mousa, Saeed; Ibrahim, Ahmed Mohamed Mahmoud (Machining science and technology, 2024)
The research aimed to study the impact of changing the stand-off distance (SOD) and traverse speed (TS) on the results of abrasive water jet (AWJ) machining on brass surfaces. The study specifically evaluated the kerf width (KW), cutting quality (CQ) and surface roughness (Ra). For this purpose, Abrasive Water Jet Machining (AWJM) was used, and adjustments were made to the SOD and TS to obtain the best cutting quality for 0.8-mm-thick brass sheets. The results showed that to achieve high cutting quality, it was necessary to reduce the SOD and increase the TS to minimize the KW. Conversely, higher TS and Ra resulted in decreased cutting quality. The largest KW was recorded at an SOD of 5 mm and TS of 90 mm/min, measuring 6.537 mm. Fine-tuning the SOD by 1 mm at the same TS produced the best machining outcomes, with a minimum KW of 1.706 mm, indicating superior cut quality. Lower cutting quality was observed at higher traverse speeds and surface roughness. The optimal Ra was achieved at 90 mm/min with an SOD of 5 mm, measuring 1.1 µm, while the maximum Ra was observed at 150 mm/min with an SOD of 1 mm, measuring 8.15 µm.